Foliar-applied urea at bloom improves early fruit growth and nitrogen status of spur leaves in pear trees, cv. Williams Bon Chretien - Curetti, Mariela (2013)
The fruit size of early ripening pear varieties is one of the most important attributes for its quality. In pear (Pyrus communis L.) the thinning effect of urea is controversial, even if urea sprays increase in general the average fruit size. We therefore tested the hypothesis that foliar-applied urea at bloom also plays an important nutritional role. Trials were carried out in two orchards of the experimental farm of the INTA Alto Valle research station, in the province of Rio Negro, Argentina on mature trees of the cv. “Williams Bon chretien” on seedling. Urea (5%, w/v) application at full bloom had a slight effect of fruit thinning of fruitlets, but increased fruit size and the number of cells per fruit. Sprayed spurs showed larger fruit weight before a significant difference in fruit number per spur was observed. The uptake of N from urea, measured by the aid 15N techniques, enhanced N concentration and contents of flowers and spur leaves by about 10%. Although we cannot exclude that the thinning effect of urea has contributed to the enhancing of the fruit size and the number of cells per fruits, our data indicated that before the thinning effect of urea occurred, the fruit size already benefited from the foliar N supply due to an enhanced leaf and flower N concentration. Due to the both the thinning and the nutritional effects, the supply of urea early of the season is therefore a powerful and relatively inexpensive tool for enhancing fruit size in pear trees.